Role of Panchayati Raj institutions for inclusive growth under Mahatma Gandhi NREGS – areview in Kerala context - C. Vinod Kumar AND R. Muthulakshmi (Indian Journal of Economics and Development, 2018)
Objective: The paper attempts to illustrate the role of Panchayati Raj Institutions for inclusive growth in rural Kerala with the implementation of Mahatma Gandhi National Employment Guarantee Scheme. Methodology/Statistical Analysis: The paper was based on the data obtained from the Management Information System of the Scheme (MIS) of Mahatma Gandhi NREGS.This MIS is the first transaction based real time system for any public work programme in the country that is available in the public domain. We can easily access the real time data for the analysis purpose. Simple Average and Percentage of some Determinants related with the scheme in four financial yearsare used to explain the subject matter of Inclusive Growth. Findings: The Mahatma Gandhi NREGS, is one of the successful schemes of Rural Development in India, has worked quite effectively in the state of Kerala. As per the Mahatma Gandhi NREG Act, Panchayati Raj Institutions have pivotal role in the planning and implementation of the scheme resulted to Local Economic Development and Inclusive Growth. It was also noticed that it has benefited in better cooperation among people and reduced the socio-economic gaps among them. Kerala State is renowned as the champion of decentralised planning; this experience effectively established the decentralised framework of planning of Mahatma Gandhi NREGS. Application: It is found that the implementation of the scheme has improved the overall standard of living of the rural households, especially marginalised sections of the society